Barriers to Creating Healthier Home Food Environments: Process Evaluation Results From 2 Home Food Environment Intervention Studies. Issue 4 (28th October 2022) - Kegler, Michelle C.; Raskind, Ilana G.; Bundy, Łucja T.; Owolabi, Shadé; Veluswamy, J. K.; Hernandez, Clarisa; Hodge, Tarccara; Haardörfer, Regine
Abstract : Few studies have identified barriers to creating a home environment more supportive of healthy eating. We examined barriers faced by participants in a randomized controlled trial and an adaptation study of the Healthy Homes/Healthy Families intervention, which uses health coaches to support low-income families in creating healthier home food environments. Coaches maintained logs of participant interactions as part of a process evaluation. We thematically analyzed logs from interactions with participants, mostly lower-income African American women (n = 114), to identify barriers for each of 8 healthy actions that serve as core elements of the intervention. Difficulty of changing current habits was a barrier for 5 of the healthy actions. No time/convenience and limited family support each influenced 2 of the healthy actions, with interpersonal barriers also stemming from social situations and visitors, including grandchildren. Cost and economic challenges were barriers for 3 of the actions. Hunger, cravings, and limited access to resources (eg, transportation, fresh fruits and vegetables) were each noted as barriers for 1 healthy action. Overall, these findings provide insight for how to better support families who are trying to improve their home food environments and highlight the need for multilevel interventions.